الظواهر المدانة في مجال التربية والتعليم - رحيم نعيمه سمر; جلال احمد ريزان (Journal of College of Education, 2020)
The education is considered one of the main and important matters for every country since it is deemed as a key for its development and its growth .This sector suffers from many essential problems , especially after 2003 , most notably reasons lying in the non- security conditions prevailing over the country . This led to losing discipline and commitment as well as respect and this ,in return caused deterioration in the education in the country and problems suffered by the teaching programs as well, most notably is the method of teaching adhered in this country and this method is deemed to be an old one. It is worthy to be mentioning that many experts and those interested in the educational programs warned to necessarily address this phenomena immediately and to not stand idle beside this matter in order not to be converted into an obstacle . Thus , in our current research we have referred to most important problems facing the education after 2003 , depending in some problems on daily and personal notes, trying to give some genuine solutions that could be applied to confront the problems.